2020
DOI: 10.1002/eco.2185
|View full text |Cite
|
Sign up to set email alerts
|

Impact of successive rainfall events on the dynamic relationship between vegetation canopies, infiltration, and recharge in engineered urban green infrastructure systems

Abstract: Soil surface crusts have been extensively studied in arid and semi‐arid regions, but not in the context of engineered urban green infrastructure (GI) systems, especially in temperate environments. Raindrop impulses can break up larger soil aggregates into smaller particles, dispersing them from their original position, and contributing to the formation of a crust at the soil surface. Crusts, in turn, can reduce infiltration and increase both runoff and the soil's susceptibility to erosion. Vegetation canopies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…Targeted design strategies may be capable of increasing synergistic relationships among soil and vegetation structures to create co-benefits. For example increasing vegetation in LID can increase infiltration [68,69], biodiversity [70], and shading, while decreasing nutrient export [71][72][73] and urban heat islands [74].…”
Section: Discussionmentioning
confidence: 99%
“…Targeted design strategies may be capable of increasing synergistic relationships among soil and vegetation structures to create co-benefits. For example increasing vegetation in LID can increase infiltration [68,69], biodiversity [70], and shading, while decreasing nutrient export [71][72][73] and urban heat islands [74].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, strong rainfall usually results in surface runoff happening faster than in rainwater infiltrate soils [35]. Previous research has proven that rainfall intensity and kinetic energy are key factors for determining the formation of runoff, and the rate of crust formation and groundwater infiltration [36][37][38]. Heavy rainfall intensity could shorten the formation time of runoff and sharply decrease the infiltrate curve [39,40].…”
Section: Discussionmentioning
confidence: 99%
“…However, this study lacked the necessary means to estimate runoff, which likely led to signi cant deviations in the nal water ux calculations. Nevertheless, previous study reported that runoff typically occurs during heavy rainfall events and increases with higher rainfall amounts (Alizadehtazi et al,2020;Liu et al, 2019;Wang et al,2015;). and when a certain critical rainfall intensity is reached, water will be lost as runoff because the soil cannot absorb and retain it, and an eventual maximum leachate ux will occur (Wang et al, 2018).…”
Section: Effect Of Rainfall On the Application Of The Water Balance M...mentioning
confidence: 95%